Analisis Inklusi Keuangan dan Pertumbuhan Inklusif terhadap Kesempatan Kerja dan Ketimpangan Pendapatan di Indonesia : Menggunakan Pendekatan Panel Simultan - Ningsih, Sri; Alfisyahri, Nuriah; Irawan, Deki; Putra, Rian (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the relationship between Financial Inclusion and Inclusive Growth in Indonesia. Financial inclusion is calculated using the Financial Inclusion Index, Inclusive Growth is measured using the Poverty Equivalent Growth Rate (PEGR) method. This study used the Simultaneous Panels data with the ILS (Indirect Least Square) method to analyze the effect of exogenous variables on endogenous variables. Utilizing secondary data, the data in this study is time series and cross-sections from 2019 – 2023. The results of this study conclude that financial inclusion in Indonesia is still "Low Inclusion" while inclusive growth in employment opportunities shows that Indonesia is in the "Not Pro Jobs" inclusive category and inclusive growth in income inequality is in the "Not Pro Poor Yet" category. The relationship between financial inclusion and inclusive growth leads to a positive and significant relationship to inclusive growth in Indonesia. These findings indicate that financial inclusion can be an important factor in achieving inclusive economic growth in Indonesia.